Reduced response of Cystathionine Beta‐Synthase (CBS) to S‐Adenosylmethionine (SAM): Identification and functional analysis of CBS gene mutations in Homocystinuria patients. Issue 2 (23rd August 2013) - Mendes, Marisa I. S.; Colaço, Henrique G.; Smith, Desirée E. C.; Ramos, Rúben J. J. F.; Pop, Ana; van Dooren, Silvy J. M.; Tavares de Almeida, Isabel; Kluijtmans, Leo A. J.; Janssen, Mirian C. H.; Rivera, Isabel; Salomons, Gajja S.; Leandro, Paula; et al.
Abstract: A reduced response of cystathionine beta‐synthase (CBS) to its allosteric activator S‐adenosylmethionine (SAM) has been reported to be a cause of CBS dysfunction in homocystinuria patients. In this work we performed a retrospective analysis of fibroblast data from 62 homocystinuria patients and found that 13 of them presented a disturbed SAM activation. Their genotypic background was identified and the corresponding CBS mutant proteins were produced in E. coli . Nine distinct mutations were detected in 22 independent alleles: the novel mutations p.K269del, p.P427L, p.S500L and p.L540Q; and the previously described mutations p.P49L, p.C165Rfs*2, p.I278T, p.R336H and p.D444N. Expression levels and residual enzyme activities, determined in the soluble fraction of E. coli lysates, strongly correlated with the localization of the affected amino acid residue. C‐terminal mutations lead to activities in the range of the wild‐type CBS and to oligomeric forms migrating faster than tetramers, suggesting an abnormal conformation that might be responsible for the lack of SAM activation. Mutations in the catalytic core were associated with low protein expression levels, decreased enzyme activities and a higher content of high molecular mass forms. Furthermore, the absence of SAM activation found in the patients' fibroblasts was confirmed for all but one of the characterized recombinant proteins (p.P49L). Our study experimentally supports a deficient regulation of CBS by SAM as a frequently found mechanism in CBS deficiency, which should be considered not only as a valuable diagnostic tool but also as a potential target for the development of new therapeutic approaches in classical homocystinuria.